2018
DOI: 10.22161/ijaers.5.4.12
|View full text |Cite
|
Sign up to set email alerts
|

Integration Readiness levels Evaluation and Systems Architecture: A Literature Review

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…LCA Environmental [11] ISO 14040/44 Energy consumed and CO2 emissions LCC Costing [12] Cash flow Unit cost SLC Social [13] Health and safety information; work conventions…”
Section: Dimension and Methods Reference Tools Examples Of Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…LCA Environmental [11] ISO 14040/44 Energy consumed and CO2 emissions LCC Costing [12] Cash flow Unit cost SLC Social [13] Health and safety information; work conventions…”
Section: Dimension and Methods Reference Tools Examples Of Variablesmentioning
confidence: 99%
“…Some authors have criticized this scale for not representing the integration of components into a complex system well, and have suggested that this integration can be measured by applying the concept of the Integration Readiness Level (IRL) [12]. Another scale is the Manufacturing Readiness Level (MRL), which focuses on the production process and was developed by the United States Department of Defense [24].…”
Section: Current Methods For Tm Assessmentmentioning
confidence: 99%